Jaw Osteosarcoma misdiagnosed as a giant aneurysmal cyst in childhood - Rachid Aloua; Ouassime Kerdoud; Faiçal Slimani (Elsevier, 2021)
A poor prognosis case of aggressive osteosarcoma of the jaw in a 12-year-old female is reported. This article is unusual in the sense that the age of onset and radiological aspects of the tumor was not in accordance with the published literature. We describe a case of Osteosarcoma misdiagnosed as a giant aneurismal bone cyst in a female child having a massive swelling over the left side of the mandible that was first diagnosed and managed to be treated as an aneurismal cyst. The case is also discussed with the review of literature of Osteosarcoma of the jaw in terms of its clinical presentation, radiologic appearances, various microscopic results, and prognosis.